THE EFFECT OF THE NEGATIVE EFFECTS OF GLOBALIZATION ON THE SPIRITUAL DEVELOPMENT OF CHALLENGING YOUTHS (Conferencea, 2022)
On the initiative of the Supreme Commander-in-Chief of the Armed Forces of the Republic of Uzbekistan, the establishment of military academic lyceums "Temurbek School" will have an important role in providing our Armed Forces with potential soldiers and officers, as well as educating and training our youth in the spirit of respect for our military-patriotic and moral values.